Othniocryptus Sharp, 1900 (Coleoptera: Erotylidae: Xenoscelinae): description of two new species from Brazil and lectotype designation for O. variegatus Sharp - Silva, Thiago J. (Zootaxa, 2026)
Two new species of Othniocryptus Sharp, 1900 are described from southeastern Brazil: Othniocryptus ypirangensis sp. nov. and Othniocryptus centromaculatus sp. nov. A lectotype is designated for O. variegatus Sharp, 1900, the type species of the genus from Panama. The male genitalia and mouthparts are described and illustrated for the first time in the genus. Diagnostic characters distinguishing the new species from O. variegatus and from each other are provided. A distribution map and an identification key for the species of the genus are also presented. The discovery of these taxa represents the first confirmed record of Xenoscelinae in Brazil. The findings highlight previously undocumented morphological variation within Othniocryptus and extend the known distribution of the genus southward into the Atlantic Forest.